Magnetism, spin dynamics, and quantum transport in two-dimensional systems. (May 2020) - Savero Torres, W.; Sierra, J.F.; Benítez, L.A.; Bonell, F.; García, J.H.; Roche, S.; Valenzuela, S.O.
Abstract: Abstract : Two-dimensional (2D) quantum materials offer a unique platform to explore mesoscopic phenomena driven by interfacial and topological effects. Their tunable electric properties and bidimensional nature enable their integration into sophisticated heterostructures with engineered properties, resulting in the emergence of new exotic phenomena not accessible in other platforms. This has fostered many studies on 2D ferromagnetism, proximity-induced effects, and quantum transport, demonstrating their relevance for fundamental research and future device applications. Here, we review ongoing progress in this lively research field with special emphasis on spin-related phenomena.